Roles of Silver Particle Immobilised in Polysulfone Mixed Matrix Membrane on Flux Enhancement and Antibacterial Properties (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
A mixed matrix membrane immobilised with silver particles has been reported to possess antibacterial properties. Nevertheless, the presence of a foreign particle such as silver inside the membrane matrix could introduce a flux resistance that reduces the water permeation. Therefore, this study investigated the influence of silver particles on the membrane by varying the silver particle dosage. The silver immobilised mixed matrix membrane was analysed using scanning electron microscopy (SEM), Fourier Transform Infrared (FTIR), X-ray diffraction (XRD), Brunauer, Emmett, and Teller (BET), and porosity tests to identify the effect of silver particles on membrane physicochemical properties. The membrane performance was evaluated by water flux and antibacterial tests. The water flux test revealed that adding silver particles in the membrane improved the water flux up to ~22 L/m2.h at 1.0 wt% silver content (PPAG1.0) compared to the pristine (PPAG0) membrane, which reported ~5 L/m2.h of flux. Further increase in silver dosage led to flux reduction, in which the membrane with 2.0 wt% (PPAG2.0) recorded ~8 L/m2.h flux. The antibacterial test indicated that the silver content in the membrane was directly proportional to the ability of a membrane to impede E. coli growth. The PPAG2.0 membrane exhibited the largest diameter of inhibition ring at 27.0 mm, while the pristine membrane did not inhibit E. coli growth. Hence, the optimum silver content in the membrane was identified at 1.0 wt% based on the PPAG1.0 membrane performance, exhibiting an inhibition diameter of 19.0 mm and ~22 L/m2.h flux.
Keywords: Silver; Antibacterial; Immobilised; Polysulfone; Mixed matrix membrane